Local Wisdom Based Coastal Community Empowerment in the Seribu Islands Administrative Regency - Airlangga, Dyan; Averus, Ahmad; Nurdin, Nurliah; Simangunsong, Fernandes (Ilomata International Journal of Management, 2026)
This study addresses the lack of an operational framework that systematically integrates local wisdom, empirical evidence, and governance mechanisms in coastal community empowerment. While previous studies have examined these elements separately, limited attention has been paid to their interaction within an integrated and context-sensitive model. This study aims to analyze the factors contributing to the ineffectiveness of empowerment programs and to develop a contextual empowerment model in Seribu Regency, DKI Jakarta. A qualitative phenomenological approach was used, involving 26 purposively selected informants, supported by observation and document analysis. The findings indicate that ineffective empowerment is driven by top-down policy design, weak institutional coordination, limited infrastructure, and dependency-oriented program implementation. At the same time, local wisdom such as cooperation, deliberation, and ecological knowledge emerge as important supporting factors when integrated into the empowerment process. This study proposes an integrative and adaptive empowerment model based on three pillars: local wisdom, evidence-based policy, and participatory governance, operationalized through a cyclical learning mechanism. This study provides a contextual and operational framework that strengthens the linkages between cultural values, empirical data, and policy practices in coastal development.